HSP70 immune reactivity and TUNEL positivity in the liver of toluene-inhaled and melatonin-treated rats - Tas, Ufuk; Ogeturk, Murat; Kuloglu, Tuncay; Sapmaz, Hilal Irmak; Kocaman, Nevin; Zararsiz, Ismail; Sarsilmaz, Mustafa (Sage Publications Inc, 2013)
Toluene is a clear, colorless and volatile hydrocarbon that is metabolized in liver, produced free oxygen radicals and can mediate cellular damage. Melatonin which is a pineal gland hormone is a very potent antioxidant. It can make the cellular membrane more durable against oxidative attacks and protect nuclear DNA from oxidative damage. This study aimed to investigate heat shock protein (HSP)70 immune reactivity and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) positivity (apoptotic activity) in the liver of toluene-inhaled and melatonin-treated rats. A total of 21 adult male Wistar albino rats were divided at random into 3 equal groups. Animals in group I were designated as control. The rats in group II were exposed to toluene (3000ppm/1h/day) for 30 days, while the rats in group III were treated with melatonin (10mg/kg/day, intraperitoneally) plus toluene inhalation. At the end of the 30-day experimental period, all rats were killed by decapitation. Then the liver tissues of rats were removed and tissue specimens were embedded in paraffin blocks. The specimens were stained with periodic acid-schiff (PAS) following routine histological procedures. Sections obtained from paraffin blocks were used for immune detection of TUNEL and HSP70. In light microscopic observations of tissues from toluene-inhaled rats, massive hepatocyte degeneration, ballooning degeneration and decreased PAS positivity were observed. Increased TUNEL positivity and HSP70 immune reactivity were determined in toluene-inhaled group and melatonin treatment decreased all these adverse effects.
Keywords: Toluene; melatonin; TUNEL; HSP70; liver